Dental implant surface modifications and osteointegration - Toledo, Valentina Andrea Ormazabal (2013)
Osteointegration can be defined as the direct contact between the living bone and the implant surface without interposed soft tissue at the microscope level and it is a critical process to guarantee implant stability and consequent short and long term clinical success. Several factors are known to influence the efficiency of the osteointegration: bone status; loading conditions; implant design and material; implant surface and surgical technique. Surface conditions are particularly important as they play a major role in the osteointegration process. Several characteristics among implant surface, such as surface composition, physic-chemical properties, surface wettability and roughness influence the rate and quality of osteointegration. Over the past three decades, the use of dental implants raised exponentially and widely expanded among the dental manufactures. The growing interest in improving the dental implant/bone interface has been addressed through the use of several techniques available for the modification of the surfaces dental implants in order to induce bioactivity. Different surface properties can induce different gene and protein expression in the osteogenic cells and also different structural and biomechanical properties to the surrounding mineralized tissue. This can result in different speed, quantity and quality of peri-implant bone formation. Nowadays, a growing aspect of endosseous implant surface research is focused on further enhancing the activity of bone forming cells at the tissue implant interface through the understanding of the fundamental processes at the interface between implant surfaces and surrounding living tissues. The goal of this study is to review the contemporary knowledge about the influencing factors affecting the osteointegration process of dental implants, analyze the currently available techniques for implant surface modification and their limitations, and also discuss the future trends in surface bioengineering and nanotechnology for improving the osteointegration and consequently enhance their biological performance.